2022
DOI: 10.1186/s12864-022-08728-w
|View full text |Cite
|
Sign up to set email alerts
|

Grade follicles transcriptional profiling analysis in different laying stages in chicken

Abstract: During follicular development, a series of key events such as follicular recruitment and selection are crucially governed by strict complex regulation. However, its molecular mechanisms remain obscure. To identify the dominant genes controlling chicken follicular development, the small white follicle (SWF), the small yellow follicle (SYF), and the large yellow follicle (LYF) in different laying stages (W22, W31, W51) were collected for RNA sequencing and bioinformatics analysis. There were 1866, 1211, and 1515… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The focal adhesion kinase, the activator of the focal adhesion pathway, is also linked to follicle development . Various species studies have shown that the ECM-receptor interaction pathway is also involved in follicle development and maturation, and that its multiple molecules can reflect follicle quality. As demonstrated in Figure A,C, YWD treatment effectively restored abnormal pathways in rats, suggesting that it may have therapeutic effects by regulating these pathways.…”
Section: Discussionmentioning
confidence: 98%
“…The focal adhesion kinase, the activator of the focal adhesion pathway, is also linked to follicle development . Various species studies have shown that the ECM-receptor interaction pathway is also involved in follicle development and maturation, and that its multiple molecules can reflect follicle quality. As demonstrated in Figure A,C, YWD treatment effectively restored abnormal pathways in rats, suggesting that it may have therapeutic effects by regulating these pathways.…”
Section: Discussionmentioning
confidence: 98%
“…The five proteins (ELN, LUM, MFAP5, COL1A2 and COL5A2) were highlighted from the protein network provided by the STRING. ELN was identified as a gene significantly related to chicken follicular development by transcriptome profiling analysis [46]. LUM has been reported to be involved in ovulation in Homo sapiens and bovine [47,48].…”
Section: Discussionmentioning
confidence: 99%
“… Ge et al (2017) ound that the extracellular region can mediate the maturation process of zebrafish oocytes. Sun et al (2022) found that the extracellular region plays a key role in follicle development in chickens. In the study, the extracellular region was the most enriched and representative pathway of the GO pathway, and we hypothesized that it might have an important role in the egg production performance of the Taihe black-bone silky fowl.…”
Section: Discussionmentioning
confidence: 99%